Energy structure transformation in the context of carbon neutralization: Evolutionary game analysis based on inclusive development of coal and clean energy. (20th April 2023) - Wang, Xin-Ping; Zhang, Zi-Ming; Guo, Zheng-Hao; Su, Chang; Sun, Lin-Hui
Abstract: Efficient utilization of the clean coal and adoption of clean energy are key points to promote energy structure transformation in the context of carbon neutrality. Considering the influence of decision makers' subjective preferences on energy structure transformation, we introduce prospect theory and psychological account theory into the evolutionary game analysis, construct an evolutionary game model with the participation of government regulators and energy consumers, and analyze the dynamic evolution of each game subject. The results of the study show that the share of coal and clean energy in energy consumption significantly affects the strategy choice of energy consumers and government regulators. The impact of the intensity of subsidies on coal and clean energy and the resulting positive externalities on the inclusive development of coal and clean energy is nonlinear. More interestingly, the strategy combination of green regulation by government regulators and integrated energy use by energy consumers is not optimal in practice due to subjective factors such as reference effects, risk preferences, and loss aversion. This study provides a new perspective on the energy mix transition based on the current situation in China.